“Analyze & Focus Your Intention” as the First Step for Applying the Digital Innovation and Transformation Process in Zoos - Wißotzki, Matthias; Wichmann, Johannes (Complex Systems Informatics and Modeling Quarterly, 2019)
In many industrial domains and service sectors, digitalization efforts show first results. New kinds of products and services were introduced, which would not have been possible without end-to-end digitalization of operational processes, continuous collection and evaluation of data about product use and evaluation of customer data or activities. Facing the challenge of customer satisfaction in terms of leisure activities, zoos are in need to modernize their tours and attendances. Therefore, this article describes the application of the Digital Innovation and Transformation Process (DITP) in animal-gardening facilities, as it collects, analyzes and structures information of 19 facilities within the “Landeszooverband Mecklenburg-Vorpommern e.V.” and combines them with qualitative studies. The research aims to analyze and focus the companies’ intention for the digitization of zoos by using the first phase of the DITP. Possible business concepts, related works and best practices were gathered and are the basis for further research and applications.